2021
DOI: 10.1093/geronb/gbab123
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Media Consumption and Avoidance With Respect to COVID-19

Abstract: Background Older versus younger adults are at greater risk from COVID-19, but descriptive data show they are less likely to seek out related information in the media, although underlying mechanisms remain unclear. Methods A representative adult lifespan sample (N = 500) completed a pre-registered online study assessing changes in media consumption in response to the pandemic, self-reported and behavioral media avoidance, avoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This study is part of a broader, ongoing program of research that examines age differences in the engagement with decision-relevant information and the decision process as a whole (for an overview, see Löckenhoff, 2018). Among other questions, this research has examined whether younger and older adults differ in the preferential acquisition of information based on its formatting and valence (e.g., Löckenhoff & Carstensen, 2007, 2008; Nolte et al, 2022), the avoidance of both hypothetical and real-world information (e.g., Deng et al, 2022; Nolte et al, 2021), and the construal of information on the basis of one’s feelings (e.g., Nolte & Löckenhoff, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a broader, ongoing program of research that examines age differences in the engagement with decision-relevant information and the decision process as a whole (for an overview, see Löckenhoff, 2018). Among other questions, this research has examined whether younger and older adults differ in the preferential acquisition of information based on its formatting and valence (e.g., Löckenhoff & Carstensen, 2007, 2008; Nolte et al, 2022), the avoidance of both hypothetical and real-world information (e.g., Deng et al, 2022; Nolte et al, 2021), and the construal of information on the basis of one’s feelings (e.g., Nolte & Löckenhoff, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The filler task was followed by the second half of the default effect task (e.g., the vacation scenario paired with the opt-out condition) as well as assessments of participants’ crystallized intelligence, cognitive reflection ability, and numeracy. In a final step, participants answered several question about their experiences during the COVID-19 pandemic that were part of a different research project (reported in Nolte et al, 2021) and are not analyzed here.…”
Section: Methodsmentioning
confidence: 99%
“…Most studies that have investigated Covid‐related information behavior can be divided into those that focus on seeking (e.g., Ebrahim et al, 2020; Huang et al, 2021; Liu, 2020; Oosterhoff and Palmer, 2020; Schäfer et al, 2021; Stainback et al, 2020; Yang et al, 2022; Zhang and Zheng, 2021), avoiding (e.g. Siebenhaar et al, 2020; Buneviciene et al, 2021; Link, 2021; Bruin et al, 2021; Qu et al, 2021; Song et al, 2021) or a combination of both, where extensive information seeking may result in overconsumption and, in turn, subsequent avoidance (Ahn et al, 2021; Dreisiebner et al, 2021; Kim et al, 2020; Liu et al, 2021; Nolte et al, 2021; Soroya et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, exposure to positive pandemic-related age stereotypes in messaging led to improvements in mental health outcomes for older adults. Nolte et al (2021) conducted an online life-span study to evaluate pandemic-related changes in media consumption. They found that older adults consumed less media and demonstrated greater behavioral media avoidance than their younger counterparts despite no difference in self-reported avoidance.…”
mentioning
confidence: 99%